Scanning Electron Microscopy of the Microcotyledonary Placenta of the Horse (Equus caballus) in the Latter Half of Gestation - Macdonald, Alastair A; Chavatte, P; Fowden, A L (Elsevier/ Harcourt Publishers Ltd, 2000)
Scanning electron microscopy was used to examine the microstructure of the maternal and fetal placenta from 25 pregnant ponies (Equus caballus) throughout the second half of gestation. Samples of placenta, 2–6 cm2in area, were collected from the antimesometrial region of the pregnant horn at 105 days (n=1), 165–219 days (n=5), 260 days (n=3), 270–277 days (n=3), 313–337 days (n=11) and immediately after spontaneous delivery at term (n=2). The maternal microcaruncle appears to be created from a clustering of about 16 uterine crypts encapsulated in a connective tissue sheath. There is a gestational increase in the depth of the microcaruncle during the second half of pregnancy. The fetal microcotyledon appears to be formed by a clustering of individual fetal villi. The length and branching of the villi increased considerably during the last 2–3 months of gestation. Tufts of from three to six branches were seen arising from close to the base of a villous stem. Branching of the villous stem occurred not only at the base but also along the secondary and tertiary branches. There was evidence of continued branching at the tips of the villi in the few days before birth.
Keywords: Scanning electron microscopy; placenta; Equus caballus; fetal villi